Value of adding fat to finishing diets to alleviate heat stress - Nichols, David A.; Ames, D.R.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred barrows, observed at temperatures of 62 and 95°F, were fed either a control or a fat added diet. Pigs housed at 95°F ate significantly less feed, gained slower, and were less efficient than littermates housed at 62°F. Fat addition to the diet did not significantly influence performance when fed at 62 or 95°F. The addition of fat did not appear to reduce heat stress or improve performance when fed at the higher temperature.
Keywords: Swine; Finishing diets; Heat stress